2010
DOI: 10.1002/bjs.6890
|View full text |Cite
|
Sign up to set email alerts
|

Management of the hernial sac in inguinal hernia repair

Abstract: Excision of the indirect hernial sac in inguinal hernia repair is associated with a lower risk of hernia recurrence than division or invagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…During a TEP repair, the hernia sac is invaginated, but a recent analysis of 48,433 operations for indirect inguinal hernia revealed that the 5-year cumulative reoperation incidence was 1.7% for hernial sac excision or division but 2.7% for invagination. 42 From randomized trials and meta-analyses, it appears that LIHR is superior to OIHR in the early postoperative period, being associated with less pain, and a shorter convalescence 5,6,37,43 but the long-term results are less clear. The present study has demonstrated that overall there is reduced postoperative chronic groin pain and numbness in those undergoing LIHR relative to an OIHR.…”
Section: Discussionmentioning
confidence: 99%
“…During a TEP repair, the hernia sac is invaginated, but a recent analysis of 48,433 operations for indirect inguinal hernia revealed that the 5-year cumulative reoperation incidence was 1.7% for hernial sac excision or division but 2.7% for invagination. 42 From randomized trials and meta-analyses, it appears that LIHR is superior to OIHR in the early postoperative period, being associated with less pain, and a shorter convalescence 5,6,37,43 but the long-term results are less clear. The present study has demonstrated that overall there is reduced postoperative chronic groin pain and numbness in those undergoing LIHR relative to an OIHR.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rates after suture repair have been reported as high as 62% [4,25,26]. When Lichtenstein introduced the open tension-free mesh repair in the 1970s, recurrence rates were greatly reduced to 0-10% [25,[27][28][29][30]. In the early 1990s, laparoscopic techniques using a tension-free mesh were developed for groin hernia repair.…”
Section: Morbidity and Mortality Of Elective Groin Hernia Repairmentioning
confidence: 99%
“…[14,16,19] , but the study conducted by G. Stylianidis et al reported that excision of the sac in indirect inguinal hernia repair is associated with lower risk of recurrence than invagination. [20] The present study had certain limitations, i.e. less number of cases, poor follow-up, short duration of follow-up, lack of parameters like quality of life after surgery.…”
Section: Discussionmentioning
confidence: 80%